2019
DOI: 10.1002/jmd2.12031
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen storage disease presenting as Cushing syndrome

Abstract: Impaired growth is common in patients with glycogen storage disease (GSD), who also may have “cherubic” facies similar to the “moon” facies of Cushing syndrome (CS). An infant presented with moon facies, growth failure, and obesity. Laboratory evaluation of the hypothalamic‐pituitary‐adrenal (HPA) axis was consistent with CS. He was subsequently found to have liver disease, hypoglycemia, and a pathogenic variant in PHKA2 , leading to the diagnosis of GSD type IXa. The cushingoid appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Cushingoid appearance, delayed motor development and osteopenia is attributed to untreated GSD Ia [ 23 , 24 ]. These complications are attributed to hypothalamic-pituitary-adrenal (HPA) axis stimulation due to chronic hypoglycemic stress causing elevated glucocorticoid secretion [ 25 ]. In our study cohort, inflammatory bowel disease (IBD) was present in 15 patients (37.5%) (see S1 Table ), that is higher as studies have reported an occasional presence of IBD in GSD Ia cases [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cushingoid appearance, delayed motor development and osteopenia is attributed to untreated GSD Ia [ 23 , 24 ]. These complications are attributed to hypothalamic-pituitary-adrenal (HPA) axis stimulation due to chronic hypoglycemic stress causing elevated glucocorticoid secretion [ 25 ]. In our study cohort, inflammatory bowel disease (IBD) was present in 15 patients (37.5%) (see S1 Table ), that is higher as studies have reported an occasional presence of IBD in GSD Ia cases [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%